The Sabar Shouchagar Project (toilets for everyone): making Nadia District the first open-defecation-free district in India. Issue 1 (19th January 2018) - Vijay, Devi; Ghosh, Debabrata
Abstract : Subject area: Public Sector Management. Study level/applicability: MBA or postgraduate program courses in public policy and management. MBA or postgraduate program courses on social innovation, social entrepreneurship and public or collective entrepreneurship. Management development programs for public policy professionals, non-governmental organizations and social enterprises. Case overview: Despite several country-wide campaigns to improve sanitation levels, India continues to be the country with the highest number of people, over 600 million, practicing open defecation. This case outlines the Sabar Shouchagar Project (Toilets for Everyone) undertaken by the District Administration of Nadia District in West Bengal that transformed the region into the first open-defecation-free district in India. The case begins with providing the context of the problem of open defecation, why it has been hard to eliminate and how undertaking a project to eliminate open-defecation-free practices has myriad institutional and economic challenges. The case then details the conceptualization and execution of the complex Sabar Shouchagar Project which involved a loose coalition of various state programs and civil society organizations. The case ends with questions on the continuity of this project beyond the tenure of the current District Magistrate and on the replicability of such an ambitious project in other parts of the country. The setting of this case, a government agency, is different than most cases and provides an opportunity for students to talk about a state agency and its interstices with civil society. This case explores how to create change through large government machinery and allows the student to explore aspects of social mobilization, social change and social innovation. If taught within a postgraduate or MBA program, the case would serve well to dispel stereotypes and biases about government bureaucracies (such as slow timelines, limited efficacy of projects and so on). Expected learning outcomes: After discussion and analysis of the case, students will be able to: appreciate how administrators within a large government bureaucracy address an ambitious and complex public health issue in a developing world context. Understand the on-the-ground challenges that arise when a change agent pursues a worthwhile goal. There are difficulties such as getting resources beyond what a government office has access to, getting alignments between different key actors within the local community and forging coalitions. Understand initiatives for social transformation within a developing country context. Specifically, the case unpacks the cultural, political, economic contexts that determine how social innovations may be pursued. Understand capacity-building and change management. Evaluate efforts required to sustain social change efforts and the challenges and pathways with respect to replication of successful social change projects in other geographies. Appreciate the design of civic engagement practices in public policy implementation. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email www.support@emeraldinsight.com to request teaching notes. Subject Code: CSS: 10: Public Sector management.